If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 1 + -4x = 4x + -5 + 1 Reorder the terms: 1 + 7x + -4x = 4x + -5 + 1 Combine like terms: 7x + -4x = 3x 1 + 3x = 4x + -5 + 1 Reorder the terms: 1 + 3x = -5 + 1 + 4x Combine like terms: -5 + 1 = -4 1 + 3x = -4 + 4x Solving 1 + 3x = -4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 1 + 3x + -4x = -4 + 4x + -4x Combine like terms: 3x + -4x = -1x 1 + -1x = -4 + 4x + -4x Combine like terms: 4x + -4x = 0 1 + -1x = -4 + 0 1 + -1x = -4 Add '-1' to each side of the equation. 1 + -1 + -1x = -4 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = -4 + -1 -1x = -4 + -1 Combine like terms: -4 + -1 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5
| 2(-5/2)^2-(-5/2)-15 | | 6x+4y=3x-8 | | j-13=46 | | 3y*2+5*2=5y*3 | | 34x+3=45 | | P+.15p=23 | | 8(n-5)=-47+8n | | 5x+4=2(X+11) | | 6+3i= | | -4(j+14)=-12 | | 17-9(.8)=3+12.8 | | x+x(0.13)=200 | | y=0.15x+40 | | -1+10x=-81 | | 6x^2=5-13x | | (11)7X(11)6= | | 3(m-14)=6 | | 4/20x=10/20 | | -18÷2/3 | | 2x+8=4x+3-2x+5 | | 15w-14w-1=6 | | 1-x=-4 | | 3(y-10)+1=-33(y-8) | | 7x+36=x | | 1+x+1-9=x-7 | | 32.7=2*pi*r | | 3r+20r-(-12)=-11 | | 2/6(4x-1) | | x+x(0.13)=1200 | | 1+x+-9=x-7 | | 5x+4(2)=-7(x-3) | | 2x/5-x-2/10=2 |